Defining and Measuring Servant Leadership Behaviour in Organizations - Sendjaya, Sen; Sarros, James C.; Santora, Joseph C. (Journal of Management Studies, 2008)
abstract This paper examines the development and initial validation of a multidimensional measure of servant leadership behaviour (Servant Leadership Behaviour Scale). Both qualitative and quantitative studies are reported to establish preliminary psychometric properties for the new 35‐item, six‐dimension measure. The resultant servant leadership model is characterized by its service orientation, holistic outlook, and moral‐spiritual emphasis, thereby extending current models of servant leadership and existing works on contemporary leadership approaches. Theoretical contributions, practical implications, and future research directions are discussed in the concluding section of the paper.